(untitled) (Medical Forum Monthly, 2020)
Objective: To find out the in-hospital outcomes and angiographic pattern of coronary artery disease in patients subjected to primary percutaneous coronary intervention (PCI) undergoing primary PCI for AMI. Study Design: A descriptive cross-sectional study. Place and Duration of Study: This study was conducted at the Department of cardiology, Chaudhry Pervaiz Elahi Institute of Cardiology, Multan January 2018 to September 2018. Materials and Methods: Among these 135 study cases, 115 (85.1%) were having male gender, and 20 (14.88%) were having female gender. In our study cases, the mean age was 47.17 ± 6.89 years (The minimum age of included cases was 30 years, on the other hand the maximum age of study cases was 60 years). Among these 135 study cases, 30 (22.2%) were having diabetes mellitus and 45 (33.3%) were having a history of hypertension. History of cigarette smoking was present in 55 (40.7%) of our study case. Family history of coronary artery disease (CAD) was present in 15 (11.1%). A successful outcome was noted in 129 (95.6%) of our study cases. Single vessel involvement was present in 90 (66.6%) of study population, involvement of two vessels by coronary artery disease was found in 25 (18.5%) of patients and multi-vessel involvement in 20 (14.8%) of our study cases. Results: A total of 135 patients fulfilling inclusion criteria of the study were recruited for study from Department of cardiology, Chaudhry Pervaiz Elahi Institute of Cardiology, Multan. Patients undergoing PCI were enrolled in the study to document in-hospital outcomes (success rate) and angiographic pattern. IBM SPSS version 18 was used to analyze the data. Conclusion: The primary percutaneous intervention is seen to be a most effective, dependable and highly effective method of coronary revascularization in the setting of acute myocardial infarction. So our study results support employing primary PCI for high success rate and desired clinical outcomes among the patients who present with acute myocardial infarction, however, there are limitations to the applicability of this modality due to lack of resources.